Relevansi Pemikiran Pendidikan Abdullah Nashih Ulwan dalam Pendidikan Islam Kontemporer - Yumni Febriani Tanjung; Yusnidar Gea; Azizah Hanum OK (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research examines the Islamic education thought of Abdullah Nashih Ulwan, a 20th century educational figure who is influential in the development of contemporary Islamic education. Ulwan offers a holistic concept of education by emphasising the cultivation of tawhid, noble character, balance, and the important role of parents and teachers. The research method used is a literature study by analysing Ulwan's main work, "Tarbiyatul Aulad fil Islam" and other relevant sources. The findings show that despite criticisms, Ulwan's thoughts are still relevant and can be implemented in modern Islamic education by adjusting strategies and methods according to the times. Ulwan emphasized the importance of instilling the values ​​of monotheism, noble morals and balance in children's education from an early age. He recommends effective educational methods, such as example, habituation, advice, educational punishment, and rewards. Apart from that, Ulwan also emphasized the important role of parents and teachers in the child's education process, as well as the importance of physical and social education for children.